Deoxynivalenol Biosynthesis in Fusarium pseudograminearum Significantly Repressed by a Megabirnavirus - Ke Li; Dongmei Liu; Xin Pan; Shuwei Yan; Jiaqing Song; Dongwei Liu; Zhifang Wang; Yuan Xie; Junli Dai; Jihong Liu; Honglian Li; Xiaoting Zhang; et al. (Toxins, 2022)
Deoxynivalenol (DON) is a mycotoxin widely detected in cereal products contaminated by Fusarium. Fusarium pseudograminearum megabirnavirus 1 (FpgMBV1) is a double-stranded RNA virus infecting Fusarium pseudograminearum. In this study, it was revealed that the amount of DON in F. pseudograminearum was significantly suppressed by FpgMBV1 through a high-performance liquid chromatography–tandem mass spectrometry (HPLC-MS/MS) assay. A total of 2564 differentially expressed genes were identified by comparative transcriptomic analysis between the FpgMBV1-containing F. pseudograminearum strain FC136-2A and the virus-free strain FC136-2A-V-. Among them, 1585 genes were up-regulated and 979 genes were down-regulated. Particularly, the expression of 12 genes (FpTRI1, FpTRI3, FpTRI4, FpTRI5, FpTRI6, FpTRI8, FpTRI10, FpTRI11, FpTRI12, FpTRI14, FpTRI15, and FpTRI101) in the trichothecene biosynthetic (TRI) gene cluster was significantly down-regulated. Specific metabolic and transport processes and pathways including amino acid and lipid metabolism, ergosterol metabolic and biosynthetic processes, carbohydrate metabolism, and biosynthesis were regulated. These results suggest an unrevealing mechanism underlying the repression of DON and TRI gene expression by the mycovirus FpgMBV1, which would provide new methods in the detoxification of DON and reducing the yield loss in wheat.